(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Consumer shopping behavior is a complex process, and several factors affect purchase decisions. In recent times, there is a drastic shift in consumer buying behavior due to technological advancements and mobile shopping applications, and consumers are very much concerned about their purchase decisions of what, where, and how to buy. Online shopping outlets use both push and pull marketing strategies for a wide range of products. Hence, online sellers redefined the business model by making consumers actively visit their online stores even though they do not intend to buy anything. Most of the time, the sellers create the demand traffic; also, impulsive purchases are made by the consumers due to the ’online deals’ or ’deal of the day.’ Several studies have reported that the family life cycle’s role is vital in understanding the consumer market for devising marketing strategies to satisfy various consumer groups’ needs. The consumer needs want, and preferences change when they move on to the next stage of the family life cycle. Thus, this study aims to draw a theoretical link between the full nest consumers, online shopping behavior determinants, and online shopping behavioral intentions by proposing a conceptual framework with research propositions. The study identified the key determinants that affect the online shopping behavioral intentions, and the appropriate theoretical linkages were provided with respect to the full nest consumers.